Demographic dynamism and socioeconomic development in Ecuador - Quiroz Cedeño, Alejandro Josue (2025)
The demographic structure of the population is a determining element in guiding public policies aimed at the country’s socioeconomic development. This article set out to analyze the influence of demographic dynamics on Ecuador’s socioeconomic development. Using a correlational quantitative approach, secondary data from the National Institute of Statistics and Censuses and the Central Bank of Ecuador (2001–2023) were analyzed for demographic and socioeconomic indicators through multiple regression models using the statistical software Stata. The results show a close relationship between the mortality rate, GDP per capita, and the young population (ages 15–24), which explain the behavior of GDP. Furthermore, it was found that employment is associated with mortality, while migratory flows have a significant impact on unemployment; together, these factors determine the variation in poverty in Ecuador, which in turn affects economic growth. The study concludes that, given the explanatory links among the variables analyzed, demographic factors shape Ecuador’s socioeconomic dynamics, underscoring the need to integrate the demographic dimension as a systemic axis in the formulation of public policies to achieve sustainable economic growth in the country.